2016
DOI: 10.1038/sj.bdj.2016.866
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis – an update for general dental practitioners

Abstract: Rheumatoid arthritis (RA) is a common chronic inflammatory autoimmune disorder which significantly impacts patients' lives and can lead to permanent disability. Inflammation in RA not only affects joints; but can affect organs including the heart and lungs. Early diagnosis, initiation of intensive drug therapy, and a multidisciplinary care approach have vastly improved the long-term prognosis for those living with the condition. However, RA patients often present with co-morbidities which add to the complexity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…5 Some studies have reported the activity of periodontal pathogens and the presence of inflammatory cytokines [interleukin-1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), and others] in systemic inflammatory diseases. 6 Cardiovascular diseases, such as atherosclerosis, showed associations with periodontitis through inflammatory markers; immune markers also presented in rheumatoid arthritis (RA), 6 especially C-reactive protein and IL-1β.…”
Section: Introductionmentioning
confidence: 99%
“…5 Some studies have reported the activity of periodontal pathogens and the presence of inflammatory cytokines [interleukin-1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), and others] in systemic inflammatory diseases. 6 Cardiovascular diseases, such as atherosclerosis, showed associations with periodontitis through inflammatory markers; immune markers also presented in rheumatoid arthritis (RA), 6 especially C-reactive protein and IL-1β.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis is a chronic inflammatory auto-immune destructive disease affecting multiple joints [34]. The older adult population with rheumatoid arthritis can be further divided into elderly-onset type which manifests after the age of 60 and young-onset type which starts at 20-40 years old [35].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…It also associates with oral complications such as periodontitis, temporomandibular joint dysfunction and its treatment can lead to methotrexate-induced oral ulceration. Moreover, the immunosuppressive effect of medications such as methotrexate and tumor necrosis factor (TNF)-α antagonists can further worsen the oral conditions [34].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 2 more Smart Citations